2005
DOI: 10.1152/ajpheart.00957.2004
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of total pulmonary arterial compliance using invasive pressure monitoring and MR flow quantification during MR-guided cardiac catheterization

Abstract: Pulmonary hypertensive disease is assessed by quantification of pulmonary vascular resistance. Pulmonary total arterial compliance is also an indicator of pulmonary hypertensive disease. However, because of difficulties in measuring compliance, it is rarely used. We describe a method of measuring pulmonary arterial compliance utilizing magnetic resonance (MR) flow data and invasive pressure measurements. Seventeen patients with suspected pulmonary hypertension or congenital heart disease requiring preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 29 publications
6
58
0
Order By: Relevance
“…Indeed, SEGERS et al [46] first showed that SV/PApp overestimates total arterial compliance by 81% in pigs and 60% in dogs when total arterial compliance was calculated using the reference method, namely the pulse pressure method. Similarly, MUTHURANGU et al [47] also reported that SV/PApp overestimates total arterial compliance by 61% in patients with suspected PH or congenital heart disease. As a result, authors initially warned against the use of the SV/PApp ratio as an estimate of total arterial compliance [7,33].…”
Section: Pulmonary Vascular Resistancementioning
confidence: 85%
See 2 more Smart Citations
“…Indeed, SEGERS et al [46] first showed that SV/PApp overestimates total arterial compliance by 81% in pigs and 60% in dogs when total arterial compliance was calculated using the reference method, namely the pulse pressure method. Similarly, MUTHURANGU et al [47] also reported that SV/PApp overestimates total arterial compliance by 61% in patients with suspected PH or congenital heart disease. As a result, authors initially warned against the use of the SV/PApp ratio as an estimate of total arterial compliance [7,33].…”
Section: Pulmonary Vascular Resistancementioning
confidence: 85%
“…Given that SV exceeds the reservoir volume of the compliant pulmonary arteries, previous studies have documented that the SV/PApp ratio may significantly overestimate total arterial compliance [46,47]. Indeed, SEGERS et al [46] first showed that SV/PApp overestimates total arterial compliance by 81% in pigs and 60% in dogs when total arterial compliance was calculated using the reference method, namely the pulse pressure method.…”
Section: Pulmonary Vascular Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…, [17]). Of note is the fact that, in the present study, the LPA and RPA boundaries were located before pulmonary artery branching, resulting in what may be seen as a simpler geometry than that used by other authors who considered multi-branched Fontan models [5,24].…”
mentioning
confidence: 99%
“…The authors use a three-element Windkessel model to compute the arterial pressures from the arterial flow. Windkessel models are derived from electrical circuit analogies, where current and voltage represent arterial flow and pressure, respectively, and have been found to represent well (after proper adjustment of the parameters) the clinical measurements [56][57][58]. To hold the mesh in space, the authors simulate the fibrous structure around the valves with springs, having one extremity attached to a basal node and the other extremity attached to a fixed point.…”
Section: Boundary Conditions: the Cardiac Phasesmentioning
confidence: 99%